Tetra-mu(2)-acetato-bis{mu(2)-5-methoxy-2- (2-morpholinoethyl)iminiometh yl phenolato}tricadmium(II) - Lair, N.M.; Ng, S.W.; Ali, Hapipah Mohd (International Union of Crystallography, 2009)
The central Cd-II atom in the trinuclear title compound, [Cd-3(C14H19N2O3)(2)(CH3COO)(4)], lies on a center of inversion and is bonded to the O atoms of four acetate groups as well as to the phenolate O atoms of the mono-deprotonated Schiff base ligands in a distorted all-trans octahedral geometry. Two of the acetate groups function in a mu(2)-bridging mode, while the other two each chelate to the terminal Cd-II atom and simultaneously bind to the central metal atom in a kappa(3)-bonding mode. The Schiff base anions N,O-chelate to the terminal metal atoms. The morpholine ring assumes a chair conformation.